EphrinB2 Inhibition and Pembrolizumab in Metastatic Urothelial Carcinoma. Issue 3 (19th August 2022) - Sadeghi, Sarmad; Quinn, David; Dorff, Tanya; Pal, Sumanta; Groshen, Susan; Tsao-Wei, Denice; Parikh, Rahul; Devitt, Michael; Parikh, Mamta; Jackovich, Alexandra; Ruel, Nora; Vogelzang, Nicholas; et al.
Abstract : PURPOSE: Patients with metastatic urothelial carcinoma have poor prognosis after failure of standard first-line chemotherapy. Immune check point programmed death 1-programmed death ligand 1 antibodies have low response rates and thus there exists a major unmet need. MATERIALS AND METHODS: In this phase II trial, patients with metastatic urothelial carcinoma that recurred or progressed after platinum-based chemotherapy received soluble EphB4-human serum albumin (sEphB4-HSA) in combination with pembrolizumab. The primary end points were tolerability and overall survival (OS). The secondary end points were progression-free survival (PFS), objective response rate (ORR), duration of response, and toxicity. The expression of sEphB4-HSA target EphrinB2 was correlated with outcomes. RESULTS: Seventy patients were enrolled. The median follow up was 22.9 months (range, 1.3-54.7). The regimen had acceptable toxicity. In the intent-to-treat analysis (N = 70), the median OS was 14.6 months (95% CI, 9.2 to 21.5). Twenty-six (37%) patients had an objective response (95% CI, 26 to 48). The median PFS was 4.1 (95% CI, 1.5 to 5.7) months. Forty-six (66%) patients expressed EphrinB2, and among them, the median OS was 21.5 months (95% CI, 12.4 to not reached), the ORR was 52% (95% CI, 37 to 67), including a complete response rate of 24% (11 of 46; 95% CI, 12 to 36). The median PFS was 5.7 (95% CI, 2.7 to 27.9) months. Response was maintained at 6, 12, and 24 months in 88%, 74%, and 69% of the patients, respectively. CONCLUSION: The combination of sEphB4-HSA and pembrolizumab appears synergistic with improved OS and ORR compared with historical data for programmed death 1/programmed death ligand 1 monotherapy.